Early urban schools: places of schooling and school buildings in Medieval, Renaissance and Early Modern Scotland up to c.1600 - Watters, Diane (The University of Edinburgh, 2021)
The history and traditions of Scottish education have been described, repeatedly and at length, in a variety of accounts by educational historians. By contrast, the architecture and built heritage of Scottish education has not. There has been no comprehensive examination of any period of Scottish school architecture, unlike those carried out in England and Wales. A detailed analysis of this building-type is well overdue. The broad research topic is Scotland’s urban schooling, school buildings, and buildings from the twelfth century (when organised ‘public’ schooling was first recorded) to c.1600. Its main focus is the emergence of medieval and late medieval grammar schooling, and where known, song schools up to the c.1450. Case studies will also examine subsequent school buildings in the sixteenth and in some instances the seventeenth century. Sites and early buildings will be identified. Early buildings were either adapted for school use (what this thesis terms ‘places of schooling’) or purpose-built school buildings. It is an interdisciplinary educational and architectural historical thesis. This thesis asks: What were the organisational and architectural patterns of early urban schooling in Scotland before c. 1600? This thesis will first establish a broad national overview of schooling and patronage as a foundation for identifying school buildings. A detailed national overview of potential locations and buildings was clearly outwith the scope of this thesis, due to the lack of pre-existing studies. Instead, this study will focus on three monastic and burgh case studies: Dunfermline, St Andrews and Edinburgh. Edinburgh will be the largest case study. Documentary, visual, and built evidence is rare. Locating school buildings is challenging, but this thesis argues that if there was a documentary record of a school, there was a location for that school, and in turn, there was a school building, or a building which housed a school. In focussing on case studies, the national story of Scotland’s early school buildings inevitably recedes. But, where possible, this thesis will identify national trends, and make civic comparisons.
Keywords: School Buildings; School Architecture; Scotland; Medieval; Early Modern; Renaissance